2008
DOI: 10.2108/zsj.25.662
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Evolution of Intronic Sequences of the β-fibrinogen Gene and Their Application in Reconstructing Mustelid Phylogeny

Abstract: Mustelidae is the largest and most diverse family in the order Carnivora. The phylogenetic relationships among the subfamilies have especially long been a focus of study. Herein we are among the first to employ two new introns (4 and 7) of the nuclear β-fibrinogen gene to clarify these enigmatic problems. In addition, two previously available nuclear (IRBP exon 1 and TTR intron 1) and one mt (ND2) data sets were also combined and analyzed simultaneously with the newly obtained sequence data in this study. Deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…1). Most of the caniform interrelationships that have increasingly been hypothesized in recent molecular multilocus studies (Flynn et al, 2000Koepfli and Wayne, 2003;Sato et al, 2003Sato et al, , 2004Sato et al, , 2006Yu et al, 2004aYu et al, , 2008Delisle and Strobeck, 2005;Strobeck, 2006, 2007;Yu and Zhang, 2006;Árnason et al, 2007;Yonezawa et al, 2007;Koepfli et al, 2008;Wolsan and Sato, 2009), and that in part were also suggested by earlier research (e.g., Wolsan, 1993a;Dragoo and Honeycutt, 1997;Bininda-Emonds et al, 1999;and references therein), are here confirmed and extended. In particular, our multigene sequence data from protein-coding exons have provided compelling evidence for a sister relationship of the monophyletic pinnipeds to the musteloids, rather than ursids, and by that our diverse analyses substantially empower the most recent molecular resolution (Yu et al, 2004a;Sato et al, 2006;Fulton and Strobeck, 2006) of considerable long-standing controversy surrounding the relationships of pinnipeds (for a review of literature, see Sato et al, 2006).…”
Section: Caniform Phylogenysupporting
confidence: 83%
See 3 more Smart Citations
“…1). Most of the caniform interrelationships that have increasingly been hypothesized in recent molecular multilocus studies (Flynn et al, 2000Koepfli and Wayne, 2003;Sato et al, 2003Sato et al, , 2004Sato et al, , 2006Yu et al, 2004aYu et al, , 2008Delisle and Strobeck, 2005;Strobeck, 2006, 2007;Yu and Zhang, 2006;Árnason et al, 2007;Yonezawa et al, 2007;Koepfli et al, 2008;Wolsan and Sato, 2009), and that in part were also suggested by earlier research (e.g., Wolsan, 1993a;Dragoo and Honeycutt, 1997;Bininda-Emonds et al, 1999;and references therein), are here confirmed and extended. In particular, our multigene sequence data from protein-coding exons have provided compelling evidence for a sister relationship of the monophyletic pinnipeds to the musteloids, rather than ursids, and by that our diverse analyses substantially empower the most recent molecular resolution (Yu et al, 2004a;Sato et al, 2006;Fulton and Strobeck, 2006) of considerable long-standing controversy surrounding the relationships of pinnipeds (for a review of literature, see Sato et al, 2006).…”
Section: Caniform Phylogenysupporting
confidence: 83%
“…In addition, as many as three out of their four topology tests failed to reject at P < 0.05 an alternative placement of the red panda relative to Mephitidae, and also their supertree analysis combining all individual gene ML trees placed the red panda in an unresolved trichotomy (with Mephitidae and a clade comprising Mustelidae and Procyonidae). All subsequent studies considering the phylogenetic arrangement hypothesized in Sato et al (2006) and Fulton and Strobeck (2006) have either found it as a poorly supported alternative to another, better supported, arrangement (Árnason et al, 2007;Fulton and Strobeck, 2007;Yu et al, 2008) or evaluated all competing arrangements as weakly supported (Yonezawa et al, 2007).…”
Section: Red Panda's Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Support for this relationship was, however, relatively weak. Most of the former multilocus molecular analyses have recovered the same phylogenetic arrangement between these two subfamilies Marmi et al, 2004;Fulton and Strobeck, 2006;Sato, 2006;Árnason et al, 2007;Schröder et al, 2009;Eizirik et al, 2010;Ki et al, 2010;Wolsan and Sato, 2010;Yamada and Masuda, 2010), whereas others placed Guloninae outside a clade containing Melinae and the morecrownward mustelids Yu and Zhang, 2006;Yu et al, 2008), hypothesized a sister relation between Melinae and Guloninae Yu et al, 2004;Fulton and Strobeck, 2006;Koepfli et al, 2008;Wolsan and Sato, 2010), or failed to resolve the relationship between the two subfamilies Fulton and Strobeck, 2006;Yu et al, 2008). The ferret-badgers (Melogale, Helictidinae) were strongly recovered as sister to a clade composed of Mustelinae, Ictonychinae, and Lutrinae (Figs.…”
Section: Establishment and Interrelationships Of Mustelid Subfamiliesmentioning
confidence: 99%